Blurring the lines: Strategic deception and self-deception in markets - Laura Gruss; Geny Piotti (Max Planck Institute for the Study of Societies, 2010)
Building on the results of a participant observation in a Chinese IT-sector company located in the northern part of China, this paper aims to clarify the nature of deception in markets. Contrary to the position of information economics and game theoretical approaches to trust, the paper argues that deception is not reducible to a question of opportunism or sending signals in order to create trustworthiness. Deception, in fact, may coexist and even be strictly entangled with self-deception, which builds on the conception of an agent whose rationality can fail or whose cognition can be biased. This paper argues that rationality failures and cognitive biases are not driven by psychological mechanisms alone. They have to be related to the social structure in which economic actors operate. In particular, the paper focuses on anticipatory socialization as one source of self-deception and the deception of others. Both types of deception are associated with a gap between aspirations and the available resources necessary for attaining them. – – Ausgehend von einer teilnehmenden Beobachtung in einem chinesischen IT-Unternehmen in Nordchina zielt dieser Artikel darauf ab, das Wesen der Täuschung in Märkten zu ergründen. Im Gegensatz zu der Position der Informationsökonomie und dem spieltheoretischen Ansatz in der Vertrauensforschung wird in diesem Artikel davon ausgegangen, dass Täuschung nicht auf Fragen des Opportunismus und der Signalsendung, die dem Aufbau von Vertrauen dient, reduziert werden kann. Täuschung kann zusammen mit Selbsttäuschung auftreten und sogar stark mit ihr verbunden sein. Selbsttäuschung baut auf dem Konzept eines Akteurs auf, dessen Rationalität versagen oder dessen Wahrnehmung verzerrt sein kann. In diesem Papier wird argumentiert, dass Rationa-litätsversagen und Wahrnehmungsverzerrung nicht nur von psychologischen Mechanismen her-vorgerufen werden, sondern mit der Sozialstruktur verbunden sind, in der der wirtschaftliche Akteur operiert. Im Besonderen konzentriert sich der Artikel auf antizipatorische Sozialisation als eine Quelle für Selbsttäuschung und Täuschung von anderen. Beide Typen der Täuschung entstehen aus der Kluft zwischen Wunschvorstellungen und den verfügbaren Ressourcen, die für ihre Realisierung notwendig sind.
Keywords: 300